2021
DOI: 10.3390/ijerph18157826
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anthropometric and Body Composition Profile in Male and Female Traditional Rowers

Abstract: The anthropometric profile has a fundamental role in rowing performance and young talent detection. The objective of this study was to analyze the anthropometric profile, body composition, and somatotype in traditional rowers, and to analyze which variables can be used as predictors of rowing performance. Twenty-four rowers competing at national level participated in this study, thirteen men and eleven women. Significant differences (p < 0.001) were observed in the height of male rowers (large effect size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
3
13
0
1
Order By: Relevance
“…For rowers, BMI values of approx. 24 kg/m 2 are considered optimal olympic rowing (Barrett and Manning, 2004;Claessens et al, 2005;Sanada et al, 2009), but the BMI of traditional rowers is sometimes higher (Penichet-Tomas et al, 2021). The mean BMI value of the elite seniors in the present study (23.72 kg/m 2 ) was very close to this benchmark, while those of all the other rowers were within normal limits (range: 20.82-23.72 kg/m 2 ).…”
Section: Anthropometric and Body Composition Profilessupporting
confidence: 58%
See 1 more Smart Citation
“…For rowers, BMI values of approx. 24 kg/m 2 are considered optimal olympic rowing (Barrett and Manning, 2004;Claessens et al, 2005;Sanada et al, 2009), but the BMI of traditional rowers is sometimes higher (Penichet-Tomas et al, 2021). The mean BMI value of the elite seniors in the present study (23.72 kg/m 2 ) was very close to this benchmark, while those of all the other rowers were within normal limits (range: 20.82-23.72 kg/m 2 ).…”
Section: Anthropometric and Body Composition Profilessupporting
confidence: 58%
“…Reports on the anthropometric characteristics of adult rowers (females and males) stress the importance of body mass (Secher and Vaage, 1983;Bourgois et al, 2000;Forjasz, 2011;Giroux et al, 2017;Maciejewski et al, 2019) and body size and proportions (Hebbelinck et al, 1980;Mikulić, 2008;Schranz et al, 2010;Majumdar et al, 2017;Penichet-Tomás et al, 2019) as determinants of success in rowing at the international level. A comparative study of male and female fixed-seat rowers revealed that body height was the best predictor of performance in male rowers, and muscle mass-in female rowers (Penichet-Tomas et al, 2021). This observation could suggest that high lean body mass and a favorable power-to-body mass ratio are better predictors of success than high body mass because increased body mass and BMI negatively impacted on career attainment (Winkert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although excess body fat can impair rowing performance, the importance of BFP in rowing compared to other sports is not entirely clear. Generally speaking, increased body mass, characterised by a high BFP and BMI, adversely affects 2000 m rowing ergometer performance [33,[71][72][73], and increased muscle mass with a high lean body mass and a favourable power-to-body mass ratio are predictors of success in rowing [32,66]. Similarly, in studies designed to determine the best performance predictive parameters [72,73], fat-free mass emerged as one of the strongest correlates with performance.…”
Section: Sex Differences In Anthropometric Characteristicsmentioning
confidence: 99%
“…Although several studies have indicated that sex differences in strength may be attributable to lean body mass (LBM), they have also reported that sex differences in power performance were still apparent regardless of body composition and muscle mass [30,31]. With regard to fixed-seat rowers (traditional rowing), Penichet-Tomas et al [32] demonstrated that in the group of the analysed variables, performance was most highly correlated with body height in male rowers and with muscle mass in female rowers. The cited authors argued that athletic success is more likely to be determined by high lean body mass and a favourable power-to-body mass ratio than by high body mass, whereas high body mass and high BMI have a detrimental effect on performance.…”
Section: Introductionmentioning
confidence: 99%
“…Slankamenac et al [16] provided specific somatotype profiles for Montenegrin karatekas, highlighting the peculiarities in body shape among different age and weight categories. Similarly, Penichet-Tomas et al [17] published anthropometric references for male and female traditional rowers. The effect of age on body composition was also evaluated by Cattem and colleagues [18] in male and female athletes, who reported that subjects older than 13 years exhibited high fluid content and cell mass using qualitative and quantitative bioimpedance-based assessments.…”
mentioning
confidence: 99%